PENGGUNAAN ALAT BANTU PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR UNDER THE BASKET SHOOT - Abi Marza Ramadhan; Agus Margono; Budhi Satyawan (PHEDHERAL, 2017)
This research aims to increase the result of under the basketball shoot on X.7th Grade in Magetan 2 Senior High School 2015 / 2016 using learning media.This research is Classroom Action Research, this research was conducted in two cycles, with each cycle consists of planning, action, observing, reflecting. The research subject are X.7th Grade in Magetan 2 Senior High School 2015 / 2016 that consist 31 students, 15 males and 16 females. The data source for this research is obtained from teachers and students. Data collection techniques are observation and assessment on volleyball service learning outcome. Technique for analyzing data is descriptive technique that is based qualitative analysis using percentage.The result of data analysis can be presented as follows, ranging from pre-action to the 1st cycle then to the 2nd cycle. On the pre-action, the students hadn’t shown good learning outcome. Very good is category on 12,9% or 4 out of 31 students, good category is on 9,67% or 3 out of 31 students, Average is category on 9,67% or 3 out of 31 students, bad category is on 51,63% or 16 out of 31 students, and very bad category is on 16,13% or 5 out of 31 students. From these data can be concluded that there are 10 students or 32,26% who pass the criteria while 21 students or 67,74% do not. On the 1st cycle, there are improvement result of under the basketball learning, very good category is 12,9% or 4 out of 31 students, good category is on 25,81% or 8 out of 31 students, average category is on 29,03% or 9 out of 31 students, Bad category is on 25,81 % or 8 out of 31 students, very bad category is on 6,45 % or 2 out of 31 students . From these data can be concluded that there are 21 students or 67,74% who pass the criteria while 10 students or 32,26% do not. On 2nd cycle, Very good category is on 16,13% % or54 out of 31 students, good category is on 35,48 % or 11 out of 31 students, average category is on 32,26% or 10 out of 31 students, bad category is on 16,13% or 5 out of 31 students, and very bad is on 0%. From these data, can be concluded that out of 31 students, 26 students or 83,87% fulfill the criteria while 5 students or 16,13% do not. From data analyz above, showing improvement the result of under the basketball shoot.Based on the result of the research can be concluded that: the use of learning media can increase the learning outcome of under the basketball shoot on X.7th Grade in Magetan 2 Senior High School 2015 / 2016.